Social challenge increases cortisol and hypothalamic monoamine levels in matrinxã (Brycon amazonicus) - Wolkers, Carla Patrícia Bejo [UNESP]; Serra, Mônica; Urbinati, Elisabeth Criscuolo (Springer, 2015)
The neural circuitry for social behavior and aggression appears to be evolutionarily conserved across the vertebrate subphylum and involves a complex neural network that includes the hypothalamus as a key structure. In the present study, we evaluated the changes in monoamine levels in the hypothalamus and on serum cortisol and plasma glucose of resident matrinxã (Brycon amazonicus) submitted to a social challenge (introduction of an intruder in their territory). The fight promoted a significant increase in hypothalamic 5-HT, NA and DA levels and on the metabolites 5-HIAA and DOPAC, and decreased 5-HIAA/5-HT and DOPAC/DA ratios in resident fish. Furthermore, an increase in serum cortisol and plasma glucose was also observed after the fight. Resident fish presented a high aggressiveness even with increased 5-HT levels in the hypothalamus. The alteration in hypothalamic monoaminergic activity of matrinxã suggests that this diencephalic region is involved in aggression and stress modulation in fish; however, it does not exclude the participation of other brain areas not tested here.
Keywords: Aggression; Cortisol; Dopamine; Hypothalamus; Noradrenaline; Serotonin; Int